Uso de insecticida botánico a base de neem para el control de plagas en el cultivo de pimiento capsicum annuum - Tituana Salinas, Elizabeth del Carmen (2006)
During the season of Febrero-Abril/06 in the farm Santa Inés of the University of Machala, was experienced in the control of plagues of the pepper with the application of extracts with the help of Neem. The planed objectives were: 1. - To evaluate the effectiveness of the botanical insecticide with the help of Neem in the control of plagues of the pepper and 2.-To determine the treatment of more yield. Were used seeds you select and disinfected of the variety long Irazú, proceeding to sow them in trays with turf as sustrato, after the germination and development of the plántulas, these you trasplantaron to the definitive field that consisted in a design the random with nine treatments and three repetitions, totalling 27 parcels or experimental units. The evaluated variables were: Identification of plagues; Percentage of attacked flowers; Percentage of affected buds; Number of fruits for plant; Weight of fruits and Yield for hectare; these they were frequently applied from three to seven days and the evaluation of the incidence of plagues was realize with frequency weekly. The insecticide products, they ready in an extractor Soxhlet using leaves, seeds of Neem, alcohol as extractante, being applied dose of 30 and 50 cc/l. of water for aspersion to foliate, the witness conventional employee was carbofuran, and the absolute one was not used any insecticide. The identified more important species were Aphis gossypii Glover and Crisomélidos of the gender Colaspis. The presence of aphids in the terminal buds registered to the week of March 22 until final of April, with populations average of 6 at 15,7 for bud staying approximately in this level five weeks, to grow up to three to four times at the end of April. The rehearsed treatments that they exercised a satisfactory control it was the oil applied to the plant and the ground. For the conventional witness, the population's tendency in the studied period went similar to that of the treatments. The production of fruits went half being ended up harvesting 5,6 tn/ha the conventional witness and 5,5 the best in the treatments with extracts of Neem. In the witness the production of fruits was low with 1,85 tn/ha. The applied treatments exercised control of the insect-plagues maintaining the incidence below the level of economic damage without ending up committing the natural control.